Sentinel lymph node biopsy in melanoma: The Oxford ten year clinical experience - Rughani, MG; Swan, M; Adams, T; Middleton, MR; Ramcharan, R; Pay, A; Birch, J; Coleman, D; Cassell, O (2011)
Sentinel lymph node biopsy (SLNB) has become an established investigation for assessing microscopic nodal metastasis in melanoma. The American Joint Committee on Cancer (AJCC) incorporates the sentinel node status in its staging criteria for melanoma. We present our clinical evaluation of performing SLNB in a single UK centre between 1998 and 2008. There were 697 patients with a mean age 53 years (range 13-92). We were able to surgically harvest at least one sentinel node in 694 patients of which 532 (76%) were negative. Of the 162 positive patients, 129 underwent further completion lymphadenectomy with 29 showing further pathologically positive nodes. At median follow up of 46 months, mortality from melanoma for SLN positive and negative patients was 32% and 4%, respectively. Disease recurrence was noted in 10% of the SLN negative group. Survival curves showed significant difference (p < 0.001) in outcomes for patients grouped by Breslow thickness. Postoperative complications were noted in 6% of patients. No life-threatening complications were noted. Our results are comparable to other national and international studies. We await the outcomes of ongoing trials to assess the therapeutic value of SLNB for melanoma. © 2011 British Association of Plastic.